Unprecedented arsenic photo-oxidation behavior of few- and multi-layer Ti3C2Tx nano-sheets. (September 2020) - Rosales, Maibelin; Garcia, Andreina; Fuenzalida, Victor M.; Espinoza-González, Rodrigo; Song, Guichen; Wang, Bo; Yu, Jinhong; Gracia, Francisco; Rosenkranz, Andreas
Highlights: Photo-oxidation performance of Ti3 C2 Tx nano-sheets regarding As removal from water. Few-layer Mxenes efficiently oxidize highly toxic As(III) to less harmful As(V). Few-layer Mxenes have a notable adsorption capability for As(III) As(V). Unprecedented dual effect of adsorption/photo-oxidation for few-layer Mxenes. Higher amount of generated OH radicals for few-layer Mxenes plays a key role. Abstract: Water contaminated by arsenic is a tremendous risk for health and environment due to its toxic and carcinogenic nature thus asking for more advanced and efficient removal strategies. Therefore, the aim of this study is to investigate for the first time the photo-oxidation performance of few- and multi-layer Ti3 C2 Tx nano-sheets (Mxenes) regarding the arsenic removal from synthetic arsenic solutions. Few-layer Mxene nano-sheets have the capability to efficiently oxidize highly toxic As(III) to less harmful As(V) and possess at the same time a notable adsorption capability for both species (about 44% for As(III) and 50% for As(V)). The quantification of photogenerated hydroxyl radicals verified that few-layer Mxene nano-sheets are capable to generate 4 times more hydroxyl radicals compared to multi-layer Mxene nano-sheets. The increase amount of produced OH radicals observed for few-layer Mxene nano-sheets can be attributed to its higher content of available active TiO2 sites, which provide more redox reaction sites thus improving the photocatalytic behavior. Moreover, the detected -OH surface terminations verified on the few-layer MXene nano-sheets promote their significant adsorption capacity. Thereby, our results demonstrate that especially few-layer Mxene nano-sheets are a promising candidate for an efficient arsenic removal due to its unprecedented dual effect of adsorption/photo-oxidation regarding this toxic contaminant. Graphical abstract: Image, graphical abstract